ISLAM, PERILAKU APARATUR SIPIL NEGARA DAN KRITIK EPISTIMOLOGI ILMU ADMINISTRASI NEGARA - RODI WAHYUDI; DEVI DESMIWAR (Lembaga Penelitian dan Pengabdian kepada Masyrakat, 2017)
The purpose of this article is to examine conceptually the epistemology of state administration science and its relation to religious and bureaucratic behavior in Indonesia. Science of state administration comes from the results of Western scientists thought. The research method used in this study is literature study. Sources of literature from books and journals. The reading result is arranged in the form of theoretical debate and followed by the interpretation of the secondary data. The results showed that the origin of the science of state administration is from the history of Europe and the West with the characteristics of value-free, secular, do not incorporate religious teachings in the formation of basic theory. Whereas the development of a country will succeed if supported by a professional and trustful bureaucracy. The nature of trust will be the form if the bureaucracy practice religious teachings. Although western nations dominate scientific papers, academic books and research journals. But as an eastern nation it is not all that comes from the West swallowed raw without judging it first.